Political Marketing Mix and Brand Personality: Implications for Voting Decisions in Legislative Elections - Nursaban Rommy Suleman; Sudirman Zaid; Suddin Lada; Andi Asari (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze and explain the influence of political marketing mix and brand personality on brand image and their implications for voting decisions for legislative candidates from the Golkar Party in Wakatobi Regency. Data collection was conducted through questionnaires and documentation. The study population consisted of 12,729 voters who selected legislative candidates from the Golkar Party in Wakatobi Regency, with a sample size of 75 respondents. The analysis tool used was SmartPLS. The results indicate that the political marketing mix significantly influences the brand image of the Golkar Party, and brand personality also affects the brand image of the Golkar Party in Wakatobi Regency. Additionally, the political marketing mix has a significant impact on voting decisions for legislative candidates from the Golkar Party, as does brand personality. Brand image itself also influences voting decisions for legislative candidates from the Golkar Party. Indirectly, the political marketing mix affects voting decisions through brand image. This study provides empirical evidence that an effective political marketing mix can enhance the brand image of candidates, thereby strengthening voters' decisions to choose legislative candidates from the Golkar Party. Furthermore, a strong brand personality positively impacts the improvement of the candidate’s brand image, ultimately reinforcing voters' decisions in favor of the Golkar Party's legislative candidates.